1990
DOI: 10.1111/j.1349-7006.1990.tb02648.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation‐specific Decrease of Phosphorylation of 80K Protein, a Substrate of Protein Kinase C, in NIH3T3 Cells

Abstract: Phosphorylation in normal and transformed NIH3T3 cells of the 80K protein, a specific substrate for protein kinase C, was compared by means of two‐dimensional gel analysis. We obtained evidence that NIH3T3 cells transformed by the c‐raf or H‐ras oncogene maintained a decreased level of phosphorylation of the 80K protein, with or without phorbol ester (TPA)‐stimulation, at all concentrations of serum tested while normal NIH3T3 cells maintained an elevated level of phosphorylation of the 80K protein. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Brooks, personal communication], although the reason for this remains unknown. However, transformation of fibroblasts by oncogenes leads to down-regulation of 80K/MARCKS Wolfman et al, 1987;Oh-uchida, et al, 1990;Reed et al, 1991;Joseph et al, 19921 and recent data from our laboratory [Goss and Brooks, 1993; and manuscript submitted] suggests that 80WMARCKS is downregulated in spontaneously transformed melanoma cells (see below). Therefore, the fact that this protein is not found in PC12 cells may simply reflect the transformed phenotype of these cells.…”
Section: Tissue Distributionmentioning
confidence: 91%
See 1 more Smart Citation
“…Brooks, personal communication], although the reason for this remains unknown. However, transformation of fibroblasts by oncogenes leads to down-regulation of 80K/MARCKS Wolfman et al, 1987;Oh-uchida, et al, 1990;Reed et al, 1991;Joseph et al, 19921 and recent data from our laboratory [Goss and Brooks, 1993; and manuscript submitted] suggests that 80WMARCKS is downregulated in spontaneously transformed melanoma cells (see below). Therefore, the fact that this protein is not found in PC12 cells may simply reflect the transformed phenotype of these cells.…”
Section: Tissue Distributionmentioning
confidence: 91%
“…Furthermore, sense clones grew to a lower saturation density, had longer doubling times and morphologically were more similar to non-transformed, quiescent Mel-ab melanocytes than antisense or vector control clones (manuscript submitted). Other workers have shown that in fibroblasts transformed with a variety of oncogenes including c-ruj Ha-rus, N-rus, K-ras, and src [Wolfman et al, 1987;Oh-uchida et al, 1990;Reed et al, 1991;Joseph et al, 19921, that a decrease in the phosphorylation and/or levels of the 80WMARCKS protein occurs. Our results extend these findings since they are the first to show that spontaneous transformation to the tumorigenic phenotype is associated with loss of phosphorylation of the protein and that both 80WMARCKS mRNA and protein levels are down-regulated compared with the normal phenotype.…”
Section: Role Of 80k/marcks In Melanocytic Cell Growth and Tumour Promentioning
confidence: 99%
“…The relevance of this phosphorylation to the acceleration of cytokinesis seen in our studies is the fact that PKC is down-regulated in many cells transformed by ras and other oncogenes [Wolfman and Macara, 1987;Weyman et al, 1988;Oh-uchida et al, 1990;Haliotis et al, 19901. Thus, in principal, a reduction in PKC activity could lead to reduced PKC-dependent phosphorylation of myosin, a reduction in inhibition of the myosin, and a pared to the nontransformed REF cells and that this is not a result of differences in cell size.…”
Section: Discussionmentioning
confidence: 83%